Two Medieval Tatar Tombstones from Kasimov. - I.V. Zaytsev (Золотоордынское обозрение, 2018)
Research objectives: Medieval Tatar epitaphs from Kasimov. Research materials: Texts found on two medieval Tatar tombstones from Kasimov. Research results and novelty: This article is a publication of the texts of two medieval Tatar tombstones from Kasimov which have been preserved in the collection of Novy Ierusalim Museum (Moscow Region). The first epitaph belongs to a certain Syun-biq-qain, the daughter of the Sultan of Qaybulla. She died on Monday at the end of Muharram 1003 AH (early October, 1594), aged 27 years. The second epitaph is partially preserved and contains neither the name nor date of death of the buried person. Both epitaphs begin by bearing Arabic Hadiths.